Adiponectin expression and the cardioprotective role of the vitamin D receptor activator paricalcitol and the angiotensin converting enzyme inhibitor enalapril in ApoE-deficient mice. (December 2014) - Suarez-Martinez, Edu; Husain, Kazim; Ferder, Leon
Background: Coronary heart disease (CHD) is the number one cause of death in the US. The adipokine adiponectin has been studied intensively for presenting and inversed association with almost every stage of CHD. For instance, the evaluation of molecules capable of enhancing endogenous adiponectin expression is well justified. In this study, we investigated the effect of the vitamin D receptor activator (VDRA) paricalcitol and the angiotensin-converting enzyme inhibitor (ACEI) enalapril on adiponectin expression, lipid profiles, adenosine monophosphate activated protein kinase (AMPK) expression, monocyte chemo-attractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNFα), cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), antioxidant capacity, CuZn-superoxide dismutase (CuZn-SOD), Mn-SOD, NADPH p22phox subunits, inducible nitric oxidesynthase (iNOS), endothelial marker eNOS, and 81 atherosclerosis-related genes in ApoE-deficient mice. Method: Seven-week-old ApoE-deficient mice were treated for 16 weeks as follows: Group 1, ApoE vehicle control (intraperitoneal [i.p.] 100 µl propylene glycol); Group 2, ApoE-paricalcitol (200 ng i.p., 3/week); Group 3, ApoE-Enalapril (30 mg/kg daily); Group 4, ApoE-paricalcitol + enalapril (described dosing); and Group 5, wild-type control (C57BLV). Results: All treated groups presented significant changes in circulating and cardiac adiponectin, cardiac cholesterol levels, AMPK, MCP-1, TNF-α, COX-2, iNOS, eNOS, CuZn-SOD, Mn-SOD and p22phox. There were 15 genes that differed in their expression, 5 of which are involved in cardioprotection and antithrombotic mechanisms: Bcl2a1a, Col3a1, Spp1 (upregulated), Itga2, and Vwf (downregulated). Conclusion: Together, our data presented a novel role for VDRA and ACEI in reducing factors associated with CHD that may lead to the discovery of new therapeutic venues.